Research on the Influence of Dust to WCDMA Signal of the Edge of Desert - Jie Chen; Na Yao (Dianxin kexue)
A modified path-loss model for the Alar terrain by taking the effect of dust and sand storm into account was proposed. A dust factor was introduced into the model by curve fitting operation from measured strength of the received signal from a WCDMA base station. The model verification was fulfilled by comparing with the measurement data in the scenario of no dust and performed via MATLAB. Finally，the simulation and comparison were given before and after optimization，which show that the optimized model is much closer to the practical communication channe1. The introduction of dust factor has a great guiding significance to the design and network layout of transmission system for mobile communications network.